2005
DOI: 10.1007/s10067-005-1087-8
|View full text |Cite
|
Sign up to set email alerts
|

Osteogenesis imperfecta: a case with hand deformities

Abstract: In a 51-year-old woman with a history of fractures and dislocations after low intensity trauma in childhood, intensive blue sclera, short stature, and hearing loss, the diagnosis of osteogenesis imperfecta (OI) was suspected. She was referred to our clinic with hand deformities and left knee pain and stiffness. She had difficulty in walking and reported a history of immobilization for 6 months because of knee pain. She had bilateral flexion contracture of the elbows which occurred following dislocations of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…Indeed, some bone diseases are characterized by alterations in bone organic composition [2][3][4]. This raises a question whether some techniques, such as electrical measurements, sensitive to changes in bone mineral density (BMD) would be also capable of detection of pathological changes in organic composition and would facilitate a more in-depth investigation of bone health.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, some bone diseases are characterized by alterations in bone organic composition [2][3][4]. This raises a question whether some techniques, such as electrical measurements, sensitive to changes in bone mineral density (BMD) would be also capable of detection of pathological changes in organic composition and would facilitate a more in-depth investigation of bone health.…”
Section: Introductionmentioning
confidence: 99%
“…The cause of this variation between these two cell types is unknown. Although the proportion of mutant collagen has not been studied in T/L cells, ligament laxity (Mirzayan et al,2000; Oz et al,2005) and tendon rupture (McKiernan,2005) have been reported in OI patients. This is consistent with the significant reduction in the mechanical strength of tail tendon (in addition to the bone defects) observed in the OI mouse model (Misof et al,1997).…”
Section: Introductionmentioning
confidence: 99%
“…Some patients with these diseases, have reported congenital joint and soft tissue contractures accompanying joint hypermobility, which is contrary to the hypothesis of this study. [46,47] In BJHS, a nonpathogenic polymorphism occurs due to minor variations in the extracellular matrix genes, for example collagen, elastin, and fibrillin. With MS, EDS and OI, major variations and variations in the protein-binding points occur in the extracellular matrix genes, leading to severe organ disorders.…”
Section: Discussionmentioning
confidence: 99%